Sarcopenia and its influencing factors in patients with stage IIIB-IV non-small cell lung cancer - S.-M. Huang; Z.-H. Zhao; C.-F. Chen; W.-D. Chen; X.-X. Pan; Y.-Y. Lu (World Cancer Research Journal)
Objective: We aimed at investigating the incidence and influencing factors of sarcopenia in patients with stage IIIB-IV non-small cell lung cancer (NSCLC).